2020
DOI: 10.1002/ijfe.1931
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between investor sentiment and earnings news in high‐ and low‐sentiment periods

Abstract: Using the Chinese equity market as the testing venue, this study explores how investor sentiment affects the immediate reaction of stock prices to earnings news in high‐ and low‐sentiment periods. Our key finding is that the sentiment‐driven pricing of earnings will differ between the two periods. Specifically, during high‐sentiment (low‐sentiment) periods, the stock price sensitivity to good (bad) earnings news increases (decreases) with investor sentiment, whereas the stock price sensitivity to bad (good) ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Lastly, we document that short selling information improves the accuracy of earnings forecasts. Similarly Li et al [5]:…”
Section: Estimation Of Epsmentioning
confidence: 89%
“…Lastly, we document that short selling information improves the accuracy of earnings forecasts. Similarly Li et al [5]:…”
Section: Estimation Of Epsmentioning
confidence: 89%
“…Further, market volatility measured with the VIX has greater influence on market returns during recessions. Li, Tian, Ouyang, and Wen (2020) concur, concluding that positive and negative sentiments lead to rises and falls in the returns of Chinese equity markets. Niţoi and Pochea (2020) examined the European markets using contagion and timevarying analysis and concluded that investors' perceptions are an important channel for the movement of markets in any direction, especially during times of crisis and economic uncertainty.…”
Section: Introductionmentioning
confidence: 91%
“…But these studies ignore the effect of investor sentiment. Based on the behavioral finance theory, a growing number of studies have found that investor sentiment has a significant impact on the market reaction to announcements in China’s stock market (Li et al, 2021). Behavioral finance theory draws on the research results of experimental psychology.…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%